Thyroid Incidentalomas in Association With Low-Dose Computed Tomography in the National Lung Screening Trial. Issue 1 (9th October 2019) - Loomans-Kropp, Holli A; Dunn, Barbara K; Kramer, Barnett S; Pinsky, Paul
Abstract: Advances in cancer screening methods have opened avenues for incidental findings and cancer overdiagnosis. We performed a secondary analysis of the National Lung Screening Trial (enrollment from 2002–2004), a randomized controlled trial comparing low-dose computed tomography (LDCT; n  = 26, 722) with chest radiography (CXR; n  = 26, 732) for lung cancer detection, to examine incidental findings related to thyroid cancer (ThCa). Three screening rounds were included, and median follow-up was 6.6 years for LDCT and 6.5 years for CXR. Radiologists reported lung and non-lung-related abnormalities. In the LDCT arm, 5.7%, 4.7%, and 4.5% of participants had abnormalities above the diaphragm (AADs) detected at baseline, year 1, and year 2, respectively, compared with 2.3%, 1.5%, and 1.3% in the CXR arm. In the LDCT arm, 205 AADs (7.0%) were thyroid-related. Overall, 60 ThCas were reported, 35 in the LDCT arm and 25 in the CXR arm ( P  = 0.2). In the LDCT arm, participants with a prior AAD had a 7.8-fold increased risk (95% confidence interval: 4.0, 15.1) of ThCa compared with those who did not have an AAD. Early and persistent excess of ThCas diagnosed earlier in the LDCT arm suggests overdiagnosis. The use of sensitive screening modalities for early detection of lung cancer might result in the discovery of thyroid incidentalomas.